Analisis Penerapan Metode Economic Order Quantity (EOQ) dan Just In Time (JIT) Pada Manajemen Pengendalian Persediaan Bahan Baku Pada PT. XYZ - Iwan Nugraha Gusniar; Muhamad Mahbub Albuhori; Diah Arum Puspita (Jurnal Ilmiah Wahana Pendidikan, 2022)
With the application of the EOQ and JIT methods, PT. XYZ can find out the right time and quantity of inventory orders and can be determined by safety stock to overcome the uncertainty of customer demand in accordance with the calculation results of the Economic Order Quantity (EOQ) and Just In Time (JIT) methods. Comparative research is used by researchers to compare inventory methods according to PT. XYZ with EOQ method and JIT method in efficiency of inventory costs and inventory optimization. The optimal quantity of raw material purchases on the EOQ method for Lever A, Lever B, Bolt, Joint, Base Ratchet, Ratchet Plate, Rod Release Assy, Equalizer, Spring Rod, Equalizer Pin, and Nut, Adjust is 10,421 on each raw material. As for the raw material, the Pawl is 22,162 and for PCV Compound it is 2,665 kg The total cost of the EOQ method on PT. XYZ of Rp. 33,571,768. The minimum inventory of just in time method of Lever A and Base Ratchet raw materials is 20,842 pcs, for Lever B, Bolt, Joint, Ratchet Plate, Rod Release Assy, Equalizer is 23,302 pcs, for Pawl is 54,285 pcs, PVC Compound is 5,331 kg, Spring Rod, Equalizer Pin, and Nut, Adjust is 27,571 pcs. The total cost of the Just In Time method at PT. XYZ of Rp. 14,766,569